Al-Lughah al-Arabiyah wa Dauruha fi Tatwiri al-Mafhum al-Hadari - Dihyatun Masqon (TSAQAFAH, 2010)
It goes without saying that Islam is not only a religion, it is also a creator and living spirit of major world civilization including Malay, with a long history stretching over fifteen centuries based mainly on wahyu as the source of all activities in various dimensions, emotional, spiritual as well as intellectual. This fact is the very reason why human being, as the most perfect creation, become the important topic of the Qur’an to act properly for the sake of reaching and endless happiness in both here and hereafter by keenly observing and understanding the milestones of this civilization through ages. Keeping in view the above reality, an organized steps should be made to enhance the process of learning and teaching of Arabic language of the future, because it is the way to rediscover the values which keep human creativities moving towards right direction for the better future of humanity. Allama Muhammad Iqbal said: “The secret of life and the essence of it is movement. I exist so long as I move, when I cease to move I shall cease to be”.